A Mouse Model of Sublethal Leptospirosis: Protocols for Infection with Leptospira Through Natural Transmission Routes, for Monitoring Clinical and Molecular Scores of Disease, and for Evaluation of the Host Immune Response. Issue 1 (3rd November 2020) - Nair, Nisha; Gomes‐Solecki, Maria
Abstract: Leptospirosis is a zoonotic disease caused by pathogenic Leptospira species that are maintained in sylvatic and domestic environments by transmission among rodents and other carriers. Humans become infected after contact of breached skin or mucosa with contaminated water or soil. Understanding persistent or sublethal infection in a host is critical for controlling human risk of exposure to pathogenic Leptospira . Animal models that recapitulate disease progression after infection via natural transmission routes are more appropriate for validation of vaccines and therapeutics. Furthermore, the ability to measure shedding of live Leptospira in urine of reservoir and carrier hosts can be used to develop new diagnostic assays and sensors to evaluate human risk of exposure. We developed inbred mouse models of Leptospirosis, that bypass survival as a criterion, in which we can analyze both pathogen and host factors affecting sublethal infection (<1 month), including shedding of Leptospira in urine. Mice are infected with pathogenic Leptospira using a physiologic route, and the clinical, histological, and molecular scores of disease are measured. Furthermore, the host immune response to Leptospira is evaluated. This mouse model also provides a tool in which to test fundamental hypotheses related to host‐pathogen interactions and the immune mechanisms engaged in protective and pathogenic immune responses. © 2020 Wiley Periodicals LLC Basic Protocol 1 : Culture and maintenance of virulent Leptospira Basic Protocol 2 : Infection of mice through a physiologic route and collection of clinical scores and biological samples Basic Protocol 3 : Analysis of pathogenesis after Leptospira infection